$\lim _{\substack{x \rightarrow 2 \\ y \rightarrow+\infty}}\left(\cos \frac{x^2}{y}\right)^{\frac{y^2+x}{x^3}}=$
【答案】 $\mathrm{e}^{-1}$.

【解析】
【解析】极限 $\lim _{\substack{x \rightarrow 2 \\ y \rightarrow+\infty}}\left(\cos \frac{x^2}{y}\right)^{\frac{y^2+x}{x^3}}=\lim _{\substack{x \rightarrow 2 \\ y \rightarrow+\infty}}\left[\left(1+\cos \frac{x^2}{y}-1\right)^{\frac{1}{\cos \frac{2}{y}-1}}\right]^{\left(\cos \frac{x^2}{y}-1\right) \cdot \frac{2^2+1}{x^3}}$,
由 $\lim _{\substack{x \rightarrow 2 \\ y \rightarrow+\infty}} \frac{x^2}{y}=0$, 知 $\lim _{\substack{x \rightarrow 2 \\ y \rightarrow+\infty}}\left(\cos \frac{x^2}{y}-1\right)=0$, 于是 $\lim _{\substack{x \rightarrow 2 \\ y \rightarrow+\infty}}\left[\left(1+\cos \frac{x^2}{y}-1\right)^{\frac{1}{\cos \frac{2}{y}} \frac{1}{y}-1}\right]=\mathrm{e}$;

$$
\lim _{\substack{x \rightarrow 2 \\ y \rightarrow+\infty}}\left[\left(\cos \frac{x^2}{y}-1\right) \cdot \frac{y^2+x}{x^3}\right]=-\frac{1}{2} \lim _{\substack{x \rightarrow 2 \\ y \rightarrow+\infty}}\left(\frac{x^4}{y^2} \cdot \frac{y^2+x}{x^3}\right)=-\frac{1}{2} \lim _{\substack{x \rightarrow 2 \\ y \rightarrow+\infty}} \frac{x y^2+x^2}{y^2}=-1,
$$
所以 $\lim _{\substack{x \rightarrow 2 \\ y \rightarrow+\infty}}\left(\cos \frac{x^2}{y}\right)^{\frac{y^2+x}{x^3}}=\mathrm{e}^{-1}$.
系统推荐